Pam Grier and the Articulation of Female Subjectivity in Blaxploitation Theme Songs. - Gunst, Stephanie. (2017)
Abstract: Discussing three films starring Pam Grier, I argue in this thesis that the theme songs within each film musically and lyrically aid in articulating a particular type of African American female subjectivity. Invoking Wayne Kostenbaum's work within diva discourse, I outline the "diva narrative" in Grier's career, from her first starring role in Coffy (1973), signifying her ascension to stardom, to Foxy Brown (1974), which anticipated not only the decline of her career but also of the Blaxploitation genre in general, to her comeback with her starring role in Quentin Tarantino's Jackie Brown (1997). While Coffy, as arguably the first female-starring action film, articulates with its three theme songs a radical female subjectivity within an ostensibly Black Power environment, Foxy Brown's one theme song ultimately translates to a return to gender norms with women as subservient to men. Reflective of the over twenty-year gap from Foxy Brown, I further postulate that Jackie Brown, through the incorporation of theme songs from various 1970s artists, articulates a new postmodern subjectivity. Little scholarship has thus far been produced on the role music plays in the articulation of African American women's subjectivity in film, and I hope with this thesis to not only fill a gap in current scholarship but also to provide more nuance and specificity to existing literature. As this thesis is quite interdisciplinary in nature, I hope the research presented here can contribute not only to musicology but also to the fields of women's studies, African American studies, and film studies.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of Music.; Advisor: Stephan Pennington.; Committee: Alessandra Campana, and Christina Sharpe.; Keywords: Music, Women's Studies, and African American Studies.